Circulating Cytokines and Venous Thromboembolism: A Bidirectional Two-Sample Mendelian Randomization Study - Hu, Teng; Su, Pengpeng; Yang, Fangkun; Ying, Jiajun; Chen, Yu; Cui, Hanbin (Thrombosis and Haemostasis, 2023)
Background Epidemiological evidence has linked circulating cytokines to venous thromboembolism (VTE). However, it remains uncertain whether these associations are causal due to confounding factors or reverse causality. We aim to explore the causality between circulating cytokines and VTE, encompassing deep vein thrombosis (DVT) and pulmonary embolism (PE).Methods In the current bidirectional Mendelian randomization (MR) study, instrumental variables of 41 circulating cytokines were obtained from the genome-wide association study meta-analyses (8,293 individuals). Summary statistics for the association of VTE (17,048 cases and 325,451 controls), DVT (8,077 cases and 295,014 controls), and PE (8,170 cases and 333,487 controls) were extracted from the FinnGen Study. A multivariable MR study was conducted to adjust for potential confounders. The inverse-variance weighted method was employed as the main analysis, and comprehensive sensitivity analyses were conducted in the supplementary analyses.Results The MR analysis indicated stromal cell-derived factor-1α was suggestively associated with a reduced risk of VTE (odds ratio [OR]: 0.90; 95% confidence interval [CI]: 0.81–0.99; p = 0.033) and DVT (OR: 0.85; 95% CI: 0.75–0.97; p = 0.015). In addition, suggestive association of granulocyte colony-stimulating factor with PE (OR: 1.20; 95% CI: 1.06-1.37; p = 0.005) was observed. Multivariable MR analysis showed that the effect of cytokines on VTE was partly mediated through hemoglobin A1c and systolic blood pressure. Reverse MR analysis revealed that VTE was linked to decreased levels of several cytokines.Conclusion We provide suggestive genetic evidence supporting the bidirectional causal effect between circulating cytokines and VTE, highlighting the importance of targeting circulating cytokines to reduce the incidence of VTE.
Keywords: cytokines; venous thromboembolism; deep vein thrombosis; pulmonary embolism; Mendelian randomization